Soybean products as a protein source in milk replacers for calves - D.P. Dawson; J.L. Morrill; P.G. Reddy; H.C. Minocha (Kansas Agricultural Experiment Station Research Reports, 1986)
Studies were conducted to evaluate two comrnercl.al soy products and one experimental soy flour as protein sources in calf milk-replacers. Further tests were conducted to produce an improved product. None of the products were as good as milk protein, with the difference being greatest in the very young calf. Calves fed milk replacers containing soy products commonly used today will not perform as well as calves fed good quality, all milk-protein, milk replacers.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Soybean products; Protein; Milk replacer